Marriage Administration Brokers: The Rational Action in the Practice of Delegating Marriage Administration in Central Lampung - Ali, Zezen Zainul (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2024)
The Indonesian law rules marriages to be registered, and the registration should be proposed by the couples to the state officials, in which cases for Muslims are recorded at the Office of Religious Affairs and for non-Muslims at the Civil Registration Office. However, some couples wittingly employ third parties—called: marriage administration brokers—to carry out all the processes. This article investigates the practice of delegating marriage administration to brokers and the underlying reasons for those delegations. This research is a field study employing a socio-legal approach, guided by rational action theory. Data were obtained through interviews and documentation. The study reveals that the practice of delegating marriage administration was carried out by the former assistant marriage registrar (P3N) and the former village head. The practice of delegating marriage administration is caused by several factors, such as the low understanding of marriage registration procedures, the assumption of complicated marriage administration, and the economic option. In this practice, the most dominant factor is the economic reason. This practice happens on ground of rational awareness in the community regarding the simplest process available, considering the benefits that are intended by both parties. The brokers (delegatees) benefit from service fees, while the couples (delegators) feel helped because they do not leave/lose their jobs should they register their marriage directly by themselves. [Hukum Indonesia mengatur bahwa pernikahan harus didaftarkan, dan pendaftaran tersebut harus diajukan oleh pasangan kepada pejabat negara, di mana bagi umat Muslim dicatatkan di Kantor Urusan Agama dan bagi non-Muslim di Kantor Catatan Sipil. Namun, beberapa pasangan dengan sengaja menggunakan pihak ketiga—disebut: calo administrasi pernikahan—untuk menjalankan seluruh prosesnya. Artikel ini menyelidiki bagaimana praktik pelimpahan administrasi pernikahan kepada calo serta alasan-alasan yang mendasari pelimpahan tersebut. Penelitian ini merupakan studi lapangan yang menggunakan pendekatan socio-legal, dengan teori tindakan rasional sebagai panduan. Data diperoleh melalui wawancara dan dokumentasi. Studi ini mengungkapkan bahwa praktik pelimpahan pendaftaran pernikahan dilakukan oleh mantan pegawai pembantu pencatat nikah (P3N) dan mantan kepala desa setempat. Praktik pelimpahan administrasi pernikahan disebabkan oleh beberapa faktor, seperti rendahnya pemahaman tentang prosedur pendaftaran pernikahan, anggapan bahwa administrasi pernikahan itu rumit, dan pilihan ekonomi. Dalam praktik ini, faktor ekonomi menjadi faktor yang paling kuat. Praktik ini berlangsung atas dasar kesadaran rasional masyarakat terhadap proses yang paling sederhana, dengan mempertimbangkan manfaat yang diharapkan oleh kedua belah pihak. Para calo (penerima pelimpahan) mendapatkan keuntungan dari biaya jasa, sementara pasangan (pemberi pelimpahan) merasa terbantu karena tidak harus meninggalkan/kehilangan pekerjaan jika mereka sendiri mendaftarkan pernikahan mereka secara langsung.]